The Effectiveness of Red Ginger To First Trimester In Pregnant Women With Emesis Gravidarum - Siti Mudrikatin (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Nausea and vomiting or emesis gravidarum are symptoms that commonly occur in pregnant women in the firs trimester and are physiological, caused by hormonal changes in pregnant women. The purpose of this study was to determine the effectiveness of giving red ginger water to reduce the frequency of emesis gravidarum in first trimester pregnant women. One Group Pre-Post Test Design research design. The research was conducted in Februari - July 2024 in the working area of the Jabon Public Health Center Jombang. The sample was 60 respondents selected with purposive sampling technique. The instrument used to measure emesis gravidarum is The Rhodes Index Nausea, Vomiting and Retching. Bivariate analysis using the Mann-Whitney test. The average difference in the frequency of emesis gravidarum before and after the intervention of red ginger extract was 3.01 and cardamom water was 2.91. The results of the Mann-Whitney test in which the intervention pretest and posttest intervention pairs of giving red ginger were a p value of 0.000 <0.05. Giving red ginger intervention is effective in reducing the nausea of emesis gravidarum significantly in reducing the frequency of emesis gravidarum.